2020
DOI: 10.1111/cp.12212
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal relations between symptoms of complicated grief, depression, and anxiety following job loss: A cross‐lagged analysis

Abstract: Objective Involuntary job loss can lead to symptoms of complicated grief (CG), depression, and anxiety. Information about the temporal linkage between these symptoms is limited and may have implications for the treatment of those suffering from mental health complaints after dismissal. The aim of this study was to explore the possible reciprocal relationships between symptoms of CG, depression, and anxiety following involuntary job loss. Method We recruited 128 Dutch workers who had lost their job within the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
2
13
0
3
Order By: Relevance
“…1. In other studies, 'job loss-related grief reactions' were called 'job loss-related complicated grief symptoms' to described the same phenomenon (Papa & Lancaster, 2016;Papa et al, 2014;Papa & Maitoza, 2013;Van Eersel et al, 2019, 2020a, 2020b. In this study, the term 'job loss-related grief reactions' was used to clarify that we are not referring to disordered grief as currently defined in DSM-5 and ICD-11 and also to emphasize that we do not argue that 'job lossrelated grief reactions' or 'job loss-related complicated grief symptoms' should be included as a novel disorder in the existing classification systems.…”
Section: Notesmentioning
confidence: 99%
See 1 more Smart Citation
“…1. In other studies, 'job loss-related grief reactions' were called 'job loss-related complicated grief symptoms' to described the same phenomenon (Papa & Lancaster, 2016;Papa et al, 2014;Papa & Maitoza, 2013;Van Eersel et al, 2019, 2020a, 2020b. In this study, the term 'job loss-related grief reactions' was used to clarify that we are not referring to disordered grief as currently defined in DSM-5 and ICD-11 and also to emphasize that we do not argue that 'job lossrelated grief reactions' or 'job loss-related complicated grief symptoms' should be included as a novel disorder in the existing classification systems.…”
Section: Notesmentioning
confidence: 99%
“…Grief reactions are characterized by separation distress combined with difficulties accepting the loss, yearning, difficulty finding meaning in life, feeling bitterness over the loss, identity confusion, and difficulty moving on with life, causing severe distress and disability on most days (Prigerson et al, 2009 ). Job loss-related grief reactions can occur in conjunction with symptoms of depression and anxiety, and may also precipitate elevations of symptoms of depression and anxiety over time (Van Eersel, Taris, & Boelen, 2020b ). Nonetheless, recent variable-centred studies have shown that depression, anxiety and grief reactions can be distinguished empirically (Papa & Maitoza, 2013 ; Van Eersel et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For most people, it stands to reason that governmentally mandated lockdowns decrease their activity levels and the number of stimuli experienced compared to pre-lockdown levels. The impact of reducing activities, stimuli and routines on the population is unknown, but various analogue situations can be used to make predictions, like death of a spouse [3]; hearing loss [4]; job loss [5]; long duration expeditions [6]; poor acculturation [7]; and even ageing when combined with loneliness [8]. Each of these situations is associated with increases in psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…ENDNOTE 1. In other studies, 'job loss-related grief reactions' were called 'job loss-related complicated grief symptoms' to described the same phenomenon , 2020a, 2020b. In this study, the term 'job loss-related grief reactions' was used to clarify that we are not referring to disordered grief as currently defined in DSM-5…”
Section: Discussionmentioning
confidence: 99%
“…Grief reactions are characterised by separation distress combined with difficulties accepting the loss, yearning, difficulty finding meaning in life, feeling bitterness over the loss, identity confusion, and difficulty moving on with life, causing severe distress and disability on most days . Job loss-related grief reactions can occur in conjunction with symptoms of depression and anxiety, and may also precipitate elevations of symptoms of depression and anxiety over time (Van Eersel et al, 2020b).…”
Section: Grief Reactions and Symptoms Of Depression And Anxiety Follo...mentioning
confidence: 99%